RhoA activation sensitizes cells to proteotoxic stimuli by abrogating the HSF1-dependent heat shock response - Meijering, Roelien A. M.; Wieland, Thomas (PLOS ONE, 2015)
Background: The heat shock response (HSR) is an ancient and highly conserved program of stress-induced gene expression, aimed at reestablishing protein homeostasis to preserve cellular fitness. Cells that fail to activate or maintain this protective response are hypersensitive to proteotoxic stress. The HSR is mediated by the heat shock transcription factor 1 (HSF1), which binds to conserved heat shock elements (HSE) in the promoter region of heat shock genes, resulting in the expression of heat shock proteins (HSP). Recently, we observed that hyperactivation of RhoA conditions cardiomyocytes for the cardiac arrhythmia atrial fibrillation. Also, the HSR is annihilated in atrial fibrillation, and induction of HSR mitigates sensitization of cells to this disease. Therefore, we hypothesized active RhoA to suppress the HSR resulting in sensitization of cells for proteotoxic stimuli. Methods and Results: Stimulation of RhoA activity significantly suppressed the proteotoxic stress-induced HSR in HL-1 atrial cardiomyocytes as determined with a luciferase reporter construct driven by the HSF1 regulated human HSP70 (HSPA1A) promoter and HSP protein expression by Western Blot analysis. Inversely, RhoA inhibition boosted the proteotoxic stress-induced HSR. While active RhoA did not preclude HSF1 nuclear accumulation, phosphorylation, acetylation, or sumoylation, it did impair binding of HSF1 to the hsp genes promoter element HSE. Impaired binding results in suppression of HSP expression and sensitized cells to proteotoxic stress. Conclusion: These results reveal that active RhoA negatively regulates the HSR via attenuation of the HSF1-HSE binding and thus may play a role in sensitizing cells to proteotoxic stimuli.